Surrogate Mother Dari Perspektif Hukum Pidana Indonesia - Siboro, Dearni Bintang Yemima; Setiabudhi, I Ketut Rai (Kertha Wicara : Journal Ilmu Hukum, 2020)
The purpose of this paper is to analyze so that we can find out the position of surrogate mother practice in Indonesian health law when applied in the health sector. The method of writing in this journal uses a normative research method in the form of a legal inventory, which refers to legislation. Indonesia has not specifically regulated surrogate mothers, but based on the formulation of offenses from the definition of criminal law according to experts, substitute mothers are actions that can be subject to sanctions based on Law Number 39 of 2009 concerning Health (hereinafter referred to as the Health Law) . Thus, technological developments in the health sector that are not accompanied by the development of laws will cause new problems such as the surrogate mother method not only against the law in Indonesia and Pancasila as the state ideology, therefore surrogate mother cannot be applied in the Indonesian health sector. Keywords: Substitute Mother, Health, Criminal Law.